Platelets - Michelson, Alan D. (Elsevier, 2013)
PLATELETS is the definitive current source of state-of-the-art knowledge about platelets and covers the entire field of platelet biology, pathophysiology, and clinical medicine. Recently there has been a rapid expansion of knowledge in both basic biology and the clinical approach to platelet-related diseases including thrombosis and hemorrhage. Novel platelet function tests, drugs, blood bank storage methods, and gene therapies have been incorporated into patient care or are in development. This book draws all this information into a single, comprehensive and authoritative resource. Comprehensive and definitive source of knowledge about platelets for clinicians, pathologists and scientists Integrates the entire field of platelet biology, pathophysiology, and clinical medicine Full color reference comprising 64 chapters, 1400 pages, and 16,000 references Contributions from 126 world leaders in their fields New chapters on topics such as the regulation of platelet life span, platelet microRNAs, GPVI and CLEC-2, monitoring of antiplatelet therapy, novel antiplatelet therapy, and making platelets ex vivo.